The prelimbic cortex is critical for context-dependent fear expression - Kim, Eun Joo; Kim, Namsoo; Kim, Hyun Taek; Choi, June-Seek (Frontiers in Behavioral Neuroscience, 2013)
The ability to regulate emotional responses in various circumstances would provide adaptive advantages for an individual. Using a context-dependent fear discrimination (CDFD) task in which the tone conditioned stimulus (CS) is paired with the footshock unconditioned stimulus (US) in one context but presented alone in another context, we investigated the role of the prelimbic cortex (PL) in contextual modulation of the conditioned fear response. After three days of CDFD training, rats froze more to the CS presented in the fearful than in the safe context. Following bilateral lesions of the PL, rats showed similar levels of freezing to the CS in both contexts, in contrast to the sham-lesioned control animals. The lesions did not impair the rats’ ability to discriminate contexts per se, as indicated by intact differential responses in a separate experiment which employed a simple context discrimination task. Consistent with the lesion data, single-unit recordings from the PL showed that the majority of CS-responsive neurons fired at a higher rate in the fearful context than in the safe context, paralleling the behavioral discrimination. Taken together, the current results suggest that the PL is involved in selective expression of conditioned fear to an explicit (tone) cue that is fully dependent on contextual information.